2021
DOI: 10.1186/s12888-021-03564-w
|View full text |Cite
|
Sign up to set email alerts
|

Subjective cognitive complaints and relations to objective cognitive performance among Lebanese patients with schizophrenia

Abstract: Background Patients with schizophrenia have a particularly low level of insight into their illness compared to people with other mental health disorders. The objectives of the study were to evaluate: 1) subjective cognitive complaints in individuals with schizophrenia in comparison with health controls, 2) the relation between subjective cognitive complaint (SCC) and objective cognitive performance in the patients group, and 3) factors related to cognitive complaint, such as depression, insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…For example, Stratta et al (2020) found a mean score of 23.34 (SD = ±14.91) when validating the SSTICS in an Italian patient population ( Stratta et al, 2020 ), while Lecardeur et al (2009) reported a mean score of 24.73 (SD = ±9.56) for patients with schizophrenia who had preserved awareness of their cognitive deficits, as measured by the SSTICS ( Lecardeur et al, 2009 ). In contrast, Haddad et al (2021) found that subjective cognitive complaints were associated with poorer cognitive performance in Lebanese patients with schizophrenia, with patients scoring 25.15 (SD = 16.67; min = 0, max = 76; median = 23.50) and controls scoring 9.15 (SD = 7.63; min = 0, max = 37; median = 7.00) ( Haddad et al, 2021 ). The lowest mean score for SSTICS among patients was reported by Baliga et al (2020) in India, with a mean score of 16.22 (SD = ± 10.8) (Baliga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Stratta et al (2020) found a mean score of 23.34 (SD = ±14.91) when validating the SSTICS in an Italian patient population ( Stratta et al, 2020 ), while Lecardeur et al (2009) reported a mean score of 24.73 (SD = ±9.56) for patients with schizophrenia who had preserved awareness of their cognitive deficits, as measured by the SSTICS ( Lecardeur et al, 2009 ). In contrast, Haddad et al (2021) found that subjective cognitive complaints were associated with poorer cognitive performance in Lebanese patients with schizophrenia, with patients scoring 25.15 (SD = 16.67; min = 0, max = 76; median = 23.50) and controls scoring 9.15 (SD = 7.63; min = 0, max = 37; median = 7.00) ( Haddad et al, 2021 ). The lowest mean score for SSTICS among patients was reported by Baliga et al (2020) in India, with a mean score of 16.22 (SD = ± 10.8) (Baliga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This scale was originally constructed and validated in parallel in the two official Canadian languages, French and English. Since its inception, there have been more than 20 publications in PubMed that employed this scale, and it has been used in clinical studies translated into five languages, namely Italian ( Stratta et al, 2020 ), Castilian ( Bengochea Seco et al, 2010 ), Mandarin/Taiwan ( Chuang et al, 2019 ), Korean ( Shin et al, 2016 ), Hindi ( Baliga et al, 2020 ), and Tunisian Arabic or SASCCS ( Johnson et al, 2009 ; Bouhamed et al, 2021 ; Haddad et al, 2021 ).…”
Section: Subjective Scale To Investigate Cognition In Schizophreniamentioning
confidence: 99%
“…When we correlated the Calgary Depressions Scale for Schizophrenia (CDSS) at baseline with SSTICS scores at the baseline, our study found no correlation with all items of the CDSS except with “7- early awakening”, where there was a significant correlation ( r = −0.256, p adjusted = 0.02). In a study assessing the first perceptions of cognition impairments and cognition functions among 120 schizophrenic patients in a psychiatric hospital in Lebanon, and 60 healthy controls using both self-assessment scales for cognitive complaints (SASCCS), and brief assessment of cognition in schizophrenia (BACS), Haddad and colleagues ( Haddad et al, 2021 ) reported positive correlations between SASCCS and CDSS scores, suggesting that patients with more depression symptoms tend to complain more about their cognitive problems. The possible reasons for different results are the difference between patients' demographics and cultural aspects between Lebanon and Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included any conditions that could impair cognitive function, such as brain injuries, neurological problems, or ongoing substance use. This study is part of a broader project and used the same methodology as a previous study [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed that a significant proportion of patients with schizophrenia had severe cognitive impairments but did not report subjective deficits or display a full awareness of their cognitive disturbances [ 27 , 28 ]. For this reason, most clinicians rely on neuropsychological assessments to determine the cognitive status of patients rather than self-report measures and often underestimate the degree of cognitive impairment in patients with schizophrenia and their ability to evaluate their cognitive deficits [ 17 ].…”
Section: Introductionmentioning
confidence: 99%